Analisis Pertumbuhan dan Fenologi Trubus pada Berbagai Struktur Tajuk Durian (Durio zybethinus) - Aris Munandar; Sri S. Harjadi; Ahmad Surkati; Bambang S. Purwoko; , Sudarsono; , Suhirman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
Two parallel experiments were conducted to study the effect of training and pruning on the growth and development of durian. Two-years old durian clones Matahari and Monthong had been pruned and or trained for 19 months as open center, central leader, palmette leader and left untreated (control treatment) in five (for Matahari) and six (for Monthong) replications. Training and pruning treatments resulted in more open crown as indicated by lower (35 - 40%) leaf area index, better growth analysis as indicated by better dry matter partition and growth rate. Relative growth rate (RGR) and net assimilation rate (NAR) of trained and pruned trees were high during 12 - 15 months after treatment, although their absolute growth rate cumulative crown dry matter low compared to untreated trees. Compared to pruning training treatment gave higher contribution to NAR. Due to wet climate of local Bogor and ontogeny of the durian used in this experiment (at late juvenile stage, 3.5 year old durian), the effect of training and pruning on the development of the durian as observed by flushing phenology had not been revealed. Flushing rhythmic pattern of treated and untreated durian were almost same. Key words: durian, tree architecture, training, pruning, phenology.